Perceived Stress, Self-Efficacy, and Mental Health of the First-Year College Students during COVID-19 Pandemic - Rona M. Guillena; Junge B. Guillena (International Journal Labs, 2022)
This study determined the relationship between the perceived stress and the mental health of the first-year college students in Adventist Medical Center College Iligan, Philippines for the Academic Year 2021-2022. This study also assessed the moderating effect of self-efficacy on the relationship between college students' perceived stress and mental health. The random sample of 208 first-year college students who were officially enrolled and those who took the online class modality for the first semester of 2021-2022. This study utilized a cross-sectional survey design and descriptive-correlation design with the application of moderated regression analysis. Results showed that perceived stress is a significant predictor of mental health. At the same time, self-efficacy does not offer any moderated effect on the relationship between perceived stress and the respondents' mental health. Thus, the perceived stress harms the students' mental health.